2016
DOI: 10.1080/09602011.2016.1247730
|View full text |Cite
|
Sign up to set email alerts
|

“Relating through sameness”: a qualitative study of friendship and social isolation in chronic traumatic brain injury

Abstract: Social isolation has been described as a common problem among traumatic brain injury (TBI) survivors during the chronic phase. Due to physical, cognitive and behavioural changes, survivors become less socially active and experience a marked decrease in the number of friends. The goal of this investigation is to explore TBI survivors' subjective account of the challenges encountered in sustaining friendships, as well as gaining insight into their particular understanding of such difficulties. Using a thematic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
37
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(50 citation statements)
references
References 54 publications
6
37
0
2
Order By: Relevance
“…This study conceptualized the development of PTG as a dynamic process within which the participants spoke of the benefits of being with others who shared similar injuries, difficulties, strengths and experiences. This resonates with recent research which describes the value of relating to others with a similar experience [40]. The participants in this study described learning and broadening their opportunities and developing as people who were less 'set in their ways' and more willing to try new and different things than they would have been previously.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…This study conceptualized the development of PTG as a dynamic process within which the participants spoke of the benefits of being with others who shared similar injuries, difficulties, strengths and experiences. This resonates with recent research which describes the value of relating to others with a similar experience [40]. The participants in this study described learning and broadening their opportunities and developing as people who were less 'set in their ways' and more willing to try new and different things than they would have been previously.…”
Section: Discussionsupporting
confidence: 81%
“…The narrative synthesise adds to the existing literature on peer support (Sweet, Noreau, Leblond, & Martin Ginis, 2016) and the importance of family and friends following SCI (Beauregard & Noreau, 2009). The findings also support recent research into the importance of relating to other people with similar injuries (Salas, Casassus, Rowlands, Pimm, & Flanagan, 2016).…”
Section: Summary Of Resultssupporting
confidence: 61%
See 1 more Smart Citation
“…The post-injury experience of friendship for these participants reflected a post-injury downhill or deteriorating process that incorporated early loss of social connections (losing contact), ongoing lack of understanding (being misunderstood) with reduced opportunities to share (wanting to share) and just hanging on to a place in society. This experience of loss and social disconnection has been reported by participants in a number of studies (Jumisko, Lexell, & Soderberg, 2005;Levack et al, 2010;Mealings, Douglas, & Olver, 2017;Muenchberger, Kendall, & Neal, 2008;Salas, Casassus, Rowlands, Pimm, & Flanagan, 2016;Shorland & Douglas, 2010), as has more frequent contact with family when compared to little or no contact with friends (Douglas, 2017(Douglas, , 2010Douglas & Spellacy, 2000). Feeling misunderstood or stigmatised has also been revealed in previous work (Knox et al, 2017;Levack et al, 2010;Mealings et al, 2017;Nochi, 1998;Salas et al, 2016).…”
Section: The Protective Nature Of Friendshipmentioning
confidence: 68%
“…In addition to close personal relationships, poor emotional perception, leading to a lack of emotional expression and an empathic response, may also help to explain why a high proportion of individuals with TBI experience deficiencies in social-interpersonal behavior that lead to a decline in social and leisure activities, diminishing social networks, poor community integration, and high levels of social isolation and loneliness (69)(70)(71)(72)(73). For instance, May et al (74) found that poor emotion recognition abilities post-injury were associated with poor social functioning and fewer independent social activities outside of the home (i.e., community integration).…”
Section: Risks Of Social Isolationmentioning
confidence: 99%